Reseach of the content of soil and graund water contaminants in the village of Ivanivka, Karlivka district, Poltava oblast - Сененко, Н. Б.; Романович, І. С.; Санжаревська, О. І.; Чала, Н. В. (Scientific Progress & Innovations, 2012)
Complex research of soil samples is done and the main physical– chemical indices of water samples from centralized and decentralized water supply in the village of Ivanivka, Karlivka district, Poltava oblast have been determined. Soil state is defined like degraded gray soil which requires regular organic fertilizer applying. Analysis of influence of water-soluble soil component on the given aquifer has been conducted. Water quality discrepancy of centralized water supply to human physiological needs has been proved, and decentralized water supply does not meet the requirements of State Sanitary Regulations and Standard.